THE STATE OF EMERGENCY AND DEMOCRACY: THE MECHANISM OF INCREASING THE AUTHORITY OF THE STATE IN MODERN LIBERAL DEMOCRACIES - Гайко, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article makes an attempt to outline the mechanism for increasing the powers of the executive power in modern liberal democracies. The phenomenon of the institution of state of emergency in the context of the political practices of modern liberal polities and the relationship between the expansion of executive power, emergency and democracy are analyzed.